Civic Education Curriculum Model in Elementary Schools in Internalizing National Values and Characters - Muhkam, Mirwan Fikri; Rahmat; Aim Abdulkarim (Journal of Practice Learning and Educational Development, 2025)
This study examines and analyzes the models and strategies in the implementation of character education in elementary schools/ madrasah Ibtidaiyah which aims to develop positive moral, ethical, and personality values in students. This research uses a qualitative approach with a literature study method by collecting sources relevant to the study of this research to be studied systematically from and comparing with character learning models in other countries in order to gain new understanding and findings. The findings of this study are (1) Involving children in social activities that begin with teaching moral values can build empathy and a sense of social responsibility (2) Civic Education learning is the main strength in integrating plural values, tolerance, historical insight, (3) The model that is relevant to the current conditions in the implementation of character education for students in elementary schools / madrasah ibtidaiyah is the exemplary model, (4) Strategies that combine character education learning with technology such as learning videos or educational games that can help students understand character values in a more fun way.